Water footprint of protein yield of field crop species based on evapotranspiration patterns - Jolánkai Márton; M. Kassai Katalin; Eser Adnan; Kempf Laura; Tarnawa Ákos (University of Szeged, Faculty of Agriculture Szeged, 2018)
Water availability is one of the major physiological factors influencing plant growth and development. An assessment study has been done at the Szent István University, Gödöllő to evaluate and identify the water footprint of protein yield of field crop species. Six field crop species (sugar beet Beta vulgaris, winter barley Hordeum vulgare, winter wheat Triticum aestivum, maize Zea mays, potato Solanum tuberosum, and alfalfa Medicago sativa) were involved in the study. Evapotranspiration patterns of the crops studied have been identified and physiologically reliable protein ranges within crop yields were evaluated. The results obtained suggest, that water footprint of cereals proved to be the lowest, however maize values were highly affected by the high variability of protein yield. Alfalfa, potato and sugar beet water footprints were in accordance with their evapotranspiration patterns.
Keywords: Mezőgazdaság-tudományok; Mezőgazdaság, erdészet, halászat